Factors Of Bloom Taxonomy And Academic Achievement: The Mediating Role Of Student’s Self-Efficacy Using Online Platforms During COVID-19 - Sayma Zia; Munaza Bibi; Ayesha Khan; Ayla Wajahat; Insiya Abbas (Kurdish Studies, 2024)
The purpose of our study is to inspect the relationship among six factors of Bloom's taxonomy with academic achievement along with a mediating role of student self-efficacy. A quantitative approach was used. While questionnaire is employed to collect the responses from students of a University in Karachi and collected information is analyzed using Smart PLS. The results of the analysis found that students remembering Understanding and creation have a positive relationship with academic achievement. Besides, student evaluation has a negative relationship with academic achievement. Whereas student’s application and analysis have no relationship with academic achievement. However, the results also showed that students’ self-efficacy mediated the relationship between all factors of Bloom's Taxonomy and academic achievement except for student analysis. Therefore, the organization needs to develop strategies regarding the effective use of online platforms along with the availability of resources for students which in turn help them in academic performance.